Clinical analysis of hyperkalemic renal tubular acidosis caused by calcineurin inhibitors in solid organ transplant recipients. (14th December 2016) - Lin, W.; Mou, L.; Tu, H.; Zhu, L.; Wang, J.; Chen, J.; Hu, Y.
Summary: What is known and objective: Calcineurin inhibitor (CNI)‐based immunosuppressive regimen is widely used for preventing rejection in solid organ transplantation. Hyperkalemic renal tubular acidosis (RTA) caused by CNI is uncommon and potentially underappreciated. We reported four such cases to increase awareness of this risk and to provide recommendations for its management based on our experience. Case summary: Four middle‐aged males underwent solid organ transplant (two kidneys, one liver, one heart) and were treated with CNI‐based immunosuppressive regimen (one cyclosporine A, three tacrolimus). On post‐operative day 13–35, hyperkalemic hyperchloremic non‐gap metabolic acidosis developed. All patients had relatively preserved renal function, normal urine output and plasma aldosterone level. Reduction in CNI dosage was partly effective; the patient on cyclosporine A was treated with fludrocortisone, and two others temporarily switched to sirolimus (SRL). What is new and conclusion: We should alert for CNI‐induced hyperkalemic RTA in transplant recipients. By CNI dosage reduction or adding low dose fludrocortisone, or temporarily switching to SRL, the prognosis of CNI‐induced hyperkalemic RTA is favourable. Abstract : Serum potassium and creatinine changes after transplantation in patient A.His potassium rose abruptly to 6.0 mmol/L on post‐operative day 13 whereas serum creatinine was 87 ?mol/L. Reduction in CNI dosage was partly effective, fludrocortisone was commenced on post‐operative day 43, hyperkalemia was subsequently normalized and renal function remained stable.